Economic Analysis of Gram Cultivation in Pakistan: Implications for Research and Extension - Qasim, Muhammad; Farooq, Umar (Annals of Arid Zone, 2016)
Increasing import bill of pulses can be minimized by enhancing pulses production in the country. Gram is a major pulse of Pakistan and is mainly grown in Bhakkar, Layyah, Mianwali and Khushab districts of Punjab. Continuous decline in area and productivity of gram has led to the need to know the factors responsible for its low production. The information was gathered from 120 farmers through a field survey in Bhakkar and Layyah districts. Cropping intensity and crop diversity index were estimated as 102% and 1.74, respectively. C-44 and Bittal-98 were most popular varieties grown in the area. Mean varietal age was 16.5 years and varietal diversity index was 1.12 indicating extremely slow varietal replacement. Majority of farmers used their own seed and recommended seed rate, while line sowing was practiced by all farmers. The proportion of farmers applying FYM, fertilizer, weedicides and pesticides was extremely low and the quantities applied were also sub-optimal. Productivity per ploughing, weeding, seed and urea applied were about 354 kg, 89 kg, 10 kg and 758 kg, respectively. The overall net income was computed as Rs. 3583 ha-1 . Returns per rupee of total and variable cost were almost 73% and 163%, respectively. Factors found significantly affecting gram productivity were urea utilization dummy, number of ploughings, per cent area weeded, planting date and seed rate. Magnitude of coefficient for urea and DAP utilization dummies, number of ploughings and gram sowing date are relatively higher than other variables. This indicates that farmers should focus more on these production practices for increasing gram yield. This also implies a need for stronger farmer-extension interaction, reinforced with increased number of improved production technology demonstration plots. Agricultural research institute in the area may reform its gram breeding agenda in favor of more drought tolerant varieties. The technology diffusion may also be enhanced through collaboration with local agricultural extension department and inputs/seed dealers of the area. In this regard, the replication of success story of Barani Village Development Program of the Punjab province is another option. Key words: Economic analysis, pulses, gram, diversity, weighted average varietal age.